2014
DOI: 10.4187/respcare.03595
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Aerosol Delivery Using Different Face Masks and Flow Rates With a High-Flow Humidity System

Abstract: BACKGROUND: Aerosol drug delivery to infants and small children is influenced by many factors, such as types of interface, gas flows, and the designs of face masks. The purpose of this in vitro study was to evaluate aerosol delivery during administration of gas flows across the range used clinically with high-flow humidity systems using 2 aerosol masks. METHODS: A spontaneous lung model was used to simulate an infant/young toddler up to 2 y of age and pediatric breathing patterns. Nebulized salbutamol by a vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Aerosol delivery in non-invasive ventilation (NIV) was proven to be of benefit and has been well studied [5,[7][8][9][10][11]. However, the effect of the change of design of nebulizers with the same mechanism on delivery has not been studied much.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol delivery in non-invasive ventilation (NIV) was proven to be of benefit and has been well studied [5,[7][8][9][10][11]. However, the effect of the change of design of nebulizers with the same mechanism on delivery has not been studied much.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol delivery via a face mask has been studied in the laboratory, but mainly in infant/pediatric models. 8,9 These studies showed that mask design, flow, and breathing pattern each independently had an effect on aerosol deposition.…”
mentioning
confidence: 99%
“…Thanks to the work of Lin et al, 1 presented in this issue of RESPIRATORY CARE, clarification of details surrounding the selection of aerosol interface with high-flow systems for infants and children has finally come to fruition. As aerosol technology has evolved, so too has evidence-based knowledge and recommendations for clinical practice.…”
mentioning
confidence: 99%
“…This implies that higher doses (or higher concentrations) of medications may be required with increased HFNC flow (Ͼ 3 L/min) or with a mask (Ͼ 12 L/min). 1 Other considerations than need to be taken into account include mask design. The incidence of drug delivered to the eyes, face, and nose is impacted by the type, size, shape, and dead space of the mask.…”
mentioning
confidence: 99%
See 1 more Smart Citation